Tissue resident memory T cells- A new benchmark for the induction of vaccine-induced mucosal immunity - Hassert, Mariah; Harty, John T. (Frontiers in Immunology, 2022)
Historically, the gold-standard benchmark for vaccine immunogenicity has been the induction of neutralizing antibodies detectable in the serum of peripheral blood. However, in recent years there has been a new appreciation for the mucosa as an important site for vaccine induced immunity. As a point of first contact, the mucosal tissue represents a major site of immune based detection and restriction of pathogen entry and dissemination. Tissue resident memory T cells (Trm) are one of the critical cell types involved in this early detection and restriction of mucosal pathogens. Following tissue-specific infection or vaccination, Trm lodge themselves within tissues and can perform rapid sensing and alarm functions to control local re-infections, in an effort that has been defined as important for restriction of a number of respiratory pathogens including influenza and respiratory syncytial virus. Despite this characterized importance, only minor attention has been paid to the importance of Trm as a benchmark for vaccine immunogenicity. The purpose of this review is to highlight the functions of Trm with particular emphasis on respiratory infections, and to suggest the inclusion of Trm elicitation as a benchmark for vaccine immunogenicity in animal models, and where possible, human samples.